EDUKASI PENCEGAHAN TINDAKAN BULLYING DI SD NEGERI 4 PED NUSA PENIDA - Anggista, Indhira; Resmiatini, Erna (FIP UNIRA MALANG, 2025)
This community service activity focuses on educating about the prevention of bullying at SD Negeri 4 Ped, Nusa Penida, an inland area with limited access to information regarding the issue of bullying. A descriptive qualitative method with a literature study was used to gain an in-depth understanding of the experiences and perspectives of students, teachers, and school staff related to bullying. This service activity involved 30 fifth and sixth-grade students, using lecture, discussion, and engaging short film screening methods. The result of this service was an increase in students' enthusiasm, courage, and self-confidence, measured by their active participation in the popcorn feedback session. This activity successfully instilled awareness and readiness in students to resist and prevent all forms of bullying.